Study of the durability of self-compacting concrete made from recycled gravel - Rachid Rabehi; Rabehi Mohamed; Omrane Mohammed (The Journal of Engineering and Exact Sciences)
Research has been carried out in Japan recently with the aim of creating concrete formulations characterized by high workability while being stable in order to adapt concrete to structures with more complex and heavily reinforced sections. (Low segregation, compaction, and bleeding) with strong mechanical properties. The result of this research is self-compacting concrete (SCC), a new type of concrete that can fulfill the aforementioned properties. SCC is distinguished by a high paste volume, a high fines volume, the use of superplasticizers, and a low gravel volume. Due to the increasing demand for aggregates, crushed gravel may be replaced with recycled gravel in the interests of environmental conservation and sustainable development goals. Steel fibers are added to recycled concrete and gravel SCCs to improve their properties. The objective of this research is to examine the durability in the hardened state as well as the physico-mechanical characteristics of self-compacting concrete (SCC) made from recycled concrete gravel. According to the results, the best recycled concrete gravel contains 50%, and the addition of 0.5% fibers improves the properties of these SCCs.